The Problems of Assessment of Debtor Bad Faith in Bankruptcy Proceedings of Natural Persons - Jokubauskas, Remigijus (Teisė, 2023)
This article analyses dishonesty of the debtor as a condition for the refusal to commence personal bankruptcy proceedings. It examines what actions may indicate the debtor’s dishonesty and how they should be interpreted. The question also arises as to whether dishonesty acts of the debtor should be interpreted in the same way, depending on the nature of the debtor, where a debtor is a consumer or an entrepreneur.